Analysis of associations and factors predicting the effectiveness of finalization in the female handball of high level - Gustavo De Conti Costa; Nilva Pessoa de Souza; Auro Barreiros Freire; José Cícero Moraes; Fabiano de Souza Fonseca; Flórence Rosana Faganello Gemente; Juracy da Silva Guimarães; Henrique de Oliveira Castro (Journal of Physical Education (Maringá), 2020)
The study aimed to analyze the association between the position of the attacker, the place of the finish and the direction of the finalization with the effectiveness of the finalization, as well as the predictive factors of this. A total of 6146 attack actions of 66 matches were analyzed by the 24 teams participating in the 2015 Women's World Handball Championship. For the association between the variables studied, we used the Chi-Square test and for predictive analysis of the data, we used the multinomial regression. The significance level of p≤0.05 was adopted and the software SPSS version 20.0 for Windows was used. The results showed an association between the finalization effect and the attacker's position (χ2 = 107.39, p = 0.0001, ɸ = 0.13), association between the finishing effect and the finishing direction (χ2 = 715, (Χ2 = 587.25, p = 0.0001, ɸ = 0.34), and that the predictive factors of the finalization effect was statistically significant (χ2 = 854.666; p <0.0001). Thus, from the results, it is possible to concluded that the effect of the finalization and the direction of the finalization, suggesting that the position of the player does not influence in obtaining the goal.